Checklist of native and invasive fishes in Aneuk Laot Lake, Sabang, Indonesia - Nurfadillah Nurfadillah; Fadli Nur; Jalil Zulkarnain; Adelyna Mohammed Akib Noor; Madewi Lis (BIO Web of Conferences)
Identification of native and invasive fish species helps in effective management of aquatic resources, including fisheries regulation, habitat restoration, and conservation. The objective of the study is to identify the native and invasive fish species found in the waters of Aneuk Laot Lake, Kota Sabang. This research was conducted from March to May 2024 in the waters of Aneuk Laot Lake. Sampling was carried out directly (sweaping) using nets measuring 1/2 inch, 3/4 inch and 1 inch. The types of fish caught in the waters of Aneuk Laot Lake consist of 4 orders, namely Cypriniformes, Cichliformes, Anabantiformes and Cyprinodontiformes. The composition of fish species in the waters of Aneuk Laot Lake, Sabang City, was identified as 6 species, namely the presence of native fish groups (native species) and invasive species. The native lake fish caught are Barbodes sp. and Rasbora sp. while the invasive fish species are Amphilophus trimaculatus, Oreochromis niloticus, Channa striata and Gambusia affinis. The diversity of fish species is useful for the management and conservation of biological resources in Aneuk Laot Lake, which is very important for the ecosystem and community of Aneuk Laot Lake, Sabang City.